Ketahanan Pangan Rumah Tangga Petani Selama Pandemi Covid-19 (Studi pada Kelompok Tani Kenanga Mulya Desa Langon) - Hafidh Irfansyah; Farida Rahmawati (Ecoplan, 2021)
This study aims to determine the level of food security of farmer households in the Kenanga Mulya farmer group, Langon Village, Ponggok District, Blitar Regency before and during the Covid-19 pandemic by analyzing the effect of the number of family members, age, income, food expenditure, and land area. The population in this study includes all members of the Kenanga Mulya farmer group, with the number of samples used in this study as many as 35 people. The data used in this study are primary data and secondary data. Preliminary data were obtained from observations and questionnaires. In contrast, secondary data were obtained from government online publications through the Central Statistics Agency (BPS) of Blitar Regency, Blitar Regency in Figures for 2019-2021, East Java Industry and Trade Office, and Information Systems for Availability and Price Development. East Java staples. Using multiple linear regression analysis techniques, this study shows that before the pandemic, income, food expenditure, and land area variables had a significant effect on food security of farmer households, the variable number of family members and age had no significant impact on farmer household food security. Meanwhile, during the pandemic, food expenditure variables and the land area had a substantial effect on the food security of farmers' households; the variables of the number of family members, age, and income did not significantly affect the food security of farmers' homes.